Evaluation of pH‐Dependent Metal Speciation Artifacts in Whole‐Cell Bioreporter Analysis. Issue 1 (1st January 2019) - Hansen, Mette Guldborg; Marcussen, Helle; Holm, Peter E.; Brandt, Kristian Koefoed
Abstract : Whole‐cell bacterial biosensors (bioreporters) are commonly applied for determination of metal toxicity and bioavailability in environmental samples. This is accomplished using a standard procedure whereby the sample is mixed with bioreporter cells suspended in a buffered medium at a fixed pH (set‐point pH assay). This experimental approach can alter the sample pH. We therefore hypothesized that metal speciation artifacts compromising our ability to use bioreporters for determination of the "true" metal bioavailability in environmental samples may be introduced. Using the copper‐specific bioreporter Pseudomonas fluorescens DF57‐Cu15 as a model, we compared the conventional set‐point pH assay to a flexible pH assay allowing for bioavailability determination at in situ sample pH. Our results demonstrate that pH‐dependent metal speciation bias may occur when using the conventional set‐point pH assay, and we recommend performing bioreporter measurements and calibrations at in situ sample pH. Although we only studied copper bioavailability, our results also have implications for bioreporter determination of other analytes displaying pH‐dependent speciation such as other metals and some organics. We call for additional bioreporter studies of chemical speciation artifacts as this represents a problem hitherto overlooked in bioreporter literature. We thus conclude that there may be considerable scope for optimization of existing bioreporter assays for assessment of environmental pollutant bioavailability. Core Ideas: Cu speciation and pH artifacts in whole‐cell bioreporter analysis were investigated. Pseudomonas fluorescens Cu bioreporter performance was strongly affected by pH. Conventional bioreporter analysis of bioavailable Cu was biased by pH artifacts. The degree of pH bias varied according to type of environmental sample. pH bias could be eliminated by use of novel flexible pH bioreporter assay.